Meta-Analysis of the Effect of Prolonged Use of High Heels on Low Back Pain in Female Sales Employees - Fadhila Firmanurulita; Agus Kristiyanto; Hanung Prasetya (Journal of Epidemiology and Public Health, 2023)
Background: Low Back Pain is the pain that is felt from the lower back area to the lower buttocks crease area (Gluteal inferior fold). One of the causes of Low Back Pain is a prolonged and excessive use of high heels. This study aims to analyze and estimate the effect of the use of high heels on Low Back Pain in sales promotion girls. Subjects and Method: Meta-analyses were carried out according to the PICO model. Population: female sales promotion employee. Intervention: Wearing High Heels. Comparison: Not using High Heels. Outcome: Low Back Pain. The article search in this study was conducted through databases that included PubMed, Google Schoolar, ScienceDirect. The keywords included: "Low Back Pain" AND "Low Back Pain" AND "High Heels" AND "Low Back Pain" "Employee sales" AND "High Heels" "Sales Low Back Pain" (aOR) "Employee sales" And "Employe sales" "Low Back Pain" AND "High Heels" AND "Employe sales", "High Heels AND High Heels" "Low Back pain Employee Sales" AND "High Heels". Full-paper articles with cross-sectional study design. The subjects of the study were users of high heels toward low back pain, the measure of association used was the adjusted odd ratio. The article selection used was PRISMA flow diagram. The analysis was performed using Revman 5.3 Results: A meta-analyss included 10 cross-sectional studies from Africa and Asia. Prolonged use of high heels increased the risk of low back pain in female sales promotion employee (aOR= 1.41; 95% CI= 1.16 to 1.171 p=0.001). Conclusion: Female sales promotion employee who wear high heels have a higher risk of experiencing low back pain. Keywords: sales promotion girl, high heels, low back pain. Correspondence:Fadhila Firmanurulita. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: missdhila18@gmail.com. Mobile. +6285740045026.